Nutrient availability affects the polar lipidome of Halimione portulacoides leaves cultured in hydroponics - Marco Custódio (Nature Portfolio, 2020)
Abstract Halophytes are increasingly regarded as suitable extractive species and co-products for coastal Integrated Multi-Trophic Aquaculture (IMTA) and studying their lipidome is a valid means towards their economic valorization. Halimione portulacoides (L.) Aellen edible leaves are rich in functional lipids with nutraceutical and pharmaceutical relevance and the present study aimed to investigate the extent to which its lipidome remains unchanged under a range of dissolved inorganic nitrogen (N) and phosphorus (P) concentrations typical of aquaculture effluents. Lipidomics analysis, done by hydrophilic interaction liquid chromatography coupled to high resolution mass spectrometry, identified 175 lipid species in the lipid extract of leaves: 140 phospholipids (PLs) and 35 glycolipids (GLs). Plants irrigated with a saline solution with 20–100 mg DIN-N L−1 and 3–15.5 mg DIP-P L−1 under a 1-week hydraulic retention time displayed a relatively stable lipidome. At lower concentrations (6 mg DIN-N L−1 and 0.8 mg DIP-P L−1), plants exhibited less PLs and GLs per unit of leaves dry weight and the GLs fraction of the lipidome changed significantly. This study reveals the importance of analyzing the lipidomic profile of halophytes under different nutritional regimens in order to establish nutrient-limitation thresholds and assure production conditions that deliver a final product with a consistent lipid profile.